Necrotizing Skin and Soft Tissue Infection Due to Syncephalastrum Species and Fusarium solani Species Complex Following Open Tibia Fracture - Vasiliki Mamali; Christos Koutserimpas; Kassiani Manoloudaki; Olympia Zarkotou; George Samonis; Georgia Vrioni (Diagnostics, 2022)
Fungal necrotizing skin and soft tissue infection (NSSTI) represents a rare clinical entity. An extremely rare case of NSSTI, following an open tibia fracture in a 36-year-old male caused by both Syncephalastrum spp. and Fusarium solani species complex (SC) is presented. The infection was diagnosed through direct microscopy, cultures and histology. The disease had a long course. The patient underwent a total of seven consecutive surgical debridements, while proper and timely antifungal treatment was initiated and included liposomal amphotericin B and voriconazole. He gradually recovered and 4 years later he is completely functioning and healthy. Invasive fungal infections are well-documented causes of high morbidity and mortality in immunocompromised individuals, whereas in immunocompetent hosts, trauma-related fungal infections have also been reported. It is of note that Syncephalastrum spp. has very rarely been identified to cause infection in immunocompromised or immunocompetent hosts, whereas Fusarium spp. has rarely been involved in skin necrotic lesions in non-immunocompromised individuals. A high suspicion index, especially in necrotic lesions in trauma patients, is pivotal for early diagnosis, which may lead to lower mortality as well as lower amputation rates. Definite diagnosis through microscopy, histology and/or cultures are of paramount importance, whereas PCR testing may also be extremely useful.